2020
DOI: 10.21203/rs.3.rs-117498/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Network Pharmacology-based Systematic Analysis of Molecular Mechanisms of Dingji Fumai Decoction for Ventricular Arrhythmia

Abstract: Background: Dingji Fumai decoction (DFD), a traditional herbal mixture, has been widely used to ventricular arrhythmia (VA) in clinical practice in China. However, research on the bioactive components and underlying mechanisms of DFD in VA is still scarce. Methods: Components of DFD were collected from TCMSP, ETCM, and literature. Then, the chemical structures of each component were obtained from PubChem. Next, SwissADME and SwissTargetPrediction were applied for compounds screening and targets prediction of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Moreover, positive cells were bigger and rounded with cytoplasmic vacuolization. These results indicated that R1D2-10 treatment led to senescence entrance triggered by telomere shortening; this was comparable with the effect of other reported telomerase inhibitors (59)(60)(61)(62)(63)(64)(65).…”
Section: Hdkc1 Residue Interactionsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, positive cells were bigger and rounded with cytoplasmic vacuolization. These results indicated that R1D2-10 treatment led to senescence entrance triggered by telomere shortening; this was comparable with the effect of other reported telomerase inhibitors (59)(60)(61)(62)(63)(64)(65).…”
Section: Hdkc1 Residue Interactionsupporting
confidence: 87%
“…All analogs complied with Lipinski's rule of five, which indicates a good druggability profile, and most showed suitable values of ADME properties using the pkCSM prediction tool, which is broadly reported (22,(76)(77)(78). Additionally, target prediction of small bioactive molecules was analyzed using Swiss Target Prediction (63,79). Small molecules are designed to bind to proteins or other macro-molecular targets to modulate their activity, resulting in phenotypic effects.…”
Section: Hdkc1 Residue Interactionmentioning
confidence: 99%
“…The binding activity is expressed as binding energy. The lower the binding energy, the more stable the docking module (30,31). In general, docking energy <-4.25 kcal/mol has docking activity, docking energy <-5 kcal/mol has good docking activity, while docking energy <-7 kcal/mol has very strong docking activity (32).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the active components and five core gene targets were matched and the docking potential was examined. The binding energy for all compounds and core genes was in the range of -8.2~-4.4 kcal/mol; the larger the absolute value of binding energy, the stronger the molecular docking effect (30,39). Only three core genes, STAT3, MPO and MMP9 had binding energy >-5 kcal/mol with active components of GEB and showed good docking activity (Table II).…”
Section: Construction and Analysis Of Herb-compound-targets-disease N...mentioning
confidence: 98%
“…A Venn diagram was used to identify the screened targets that were shared by GD and DF. The common targets were considered the therapeutic targets of GD in the treatment of DF, as described previously (Liang et al 2021). The STRING database (https://cn.string-db.org/) was used to construct a target protein-protein interaction (PPI) network (Szklarczyk et al 2019).…”
Section: Construction Of the Intersection Network And Ppi Networkmentioning
confidence: 99%